2021
DOI: 10.3389/fnins.2021.652817
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Disturbed the Tryptophan Catabolites in Hippocampus of Post-operative Fatigue Syndrome Rats via Indoleamine 2,3-Dioxygenas Enzyme and the Improvement Effect of Ginsenoside Rb1

Abstract: AimPost-operative fatigue syndrome (POFS) is a common complication that prolongs the recovery to normal function and activity after surgery. The aim of the present study was to explore the mechanism of central fatigue in POFS and the anti-fatigue effect of ginsenoside Rb1.MethodWe investigated the association between inflammation, indoleamine 2,3-dioxygenase (IDO) enzyme, and tryptophan metabolism in the hippocampus of POFS rats. A POFS rat model was induced by major small intestinal resection. Rats with major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We recently reported that in patients with chronic kidney disease undergoing hemodialysis, IDO activity was significantly associated with fatigue and IL-6 levels [25]. Also considering another study on rats after major abdominal surgery the increase of inflammatory cytokines in the hippocampus and the consequent upregulation of the kynurenine pathway mediated by the overexpression of the IDO enzyme through the p38MAPK-NF-κB/p65 pathway results in fatigue behaviors especially in the early phase after surgery [26]. Taken together, this evidence show a close relation among central fatigue, Kyn and Trp levels and inflammation.…”
Section: Kynurenine Pathway and Effect On Neuronal Function During Ca...mentioning
confidence: 97%
“…We recently reported that in patients with chronic kidney disease undergoing hemodialysis, IDO activity was significantly associated with fatigue and IL-6 levels [25]. Also considering another study on rats after major abdominal surgery the increase of inflammatory cytokines in the hippocampus and the consequent upregulation of the kynurenine pathway mediated by the overexpression of the IDO enzyme through the p38MAPK-NF-κB/p65 pathway results in fatigue behaviors especially in the early phase after surgery [26]. Taken together, this evidence show a close relation among central fatigue, Kyn and Trp levels and inflammation.…”
Section: Kynurenine Pathway and Effect On Neuronal Function During Ca...mentioning
confidence: 97%
“…[26] Additionally, Rb3 can inhibit the phosphorylation level of p38MAPK and p65 NF-кB, reduce the expression of total AKT, significantly reduce the protein expression levels of IL-1β, IL-6, and IL-8, and reduce the expression of total-AKT simultaneously, resulting in the reduction of inflammatory response caused by LPS by inhibiting the MAPK/AKT signaling pathway. [27] Liu et al [28] used ginsenoside Rb1 in the treatment of postoperative fatigue syndrome (POFS). ELISA and real-time PCR were used to evaluate the levels of inflammatory cytokines in serum and the hippocampus, respectively.…”
Section: Participation In Mapk Signaling Pathwaymentioning
confidence: 99%
“…Pro-inflammatory cytokines increase the activity of indoleamine 2,3-dioxygenase (IDO), which converts tryptophan, the primary amino acid of serotonin, into kynurenine [122]. Hence, increased IDO activity in response to inflammation leads to serotonin depletion in the brain, as observed in animal models [163,164]. In human studies, IFN-α therapy led to increased kynurenine and decreased tryptophan levels that were associated with symptoms of depression and anxiety, as well as cognitive problems, including memory disturbances and confusion [165,166].…”
Section: Impact Of Inflammation On Brain and Behaviormentioning
confidence: 99%